Giant-cell arteritis without cranial manifestations: Working diagnosis of a distinct disease pattern. Issue 26 (June 2016) - de Boysson, Hubert; Lambert, Marc; Liozon, Eric; Boutemy, Jonathan; Maigné, Gwénola; Ollivier, Yann; Ly, Kim; Manrique, Alain; Bienvenu, Boris; Aouba, Achille
Abstract : Abstract: Diagnosis of giant-cell arteritis (GCA) is challenging in the absence of cardinal cranial symptoms/signs. We aimed to describe the clinical presentation, diagnostic process, and disease course of GCA patients without cranial symptoms, and to compare them to those of patients with typical cranial presentation. In this retrospective multicenter study, we enrolled patients with GCA who satisfied at least 3 of the 5 American College of Rheumatology criteria for GCA, or 2 criteria associated with contributory vascular biopsy other than temporal artery biopsy or with demonstration of large-vessel involvement; underwent iconographic evaluation of large arterial vessels (aortic CT scan or a positron emission tomography with 18 F-fluorodeoxyglucose combined with computed tomography (FDG-PET/CT) scan or cardiac echography combined with a large-vessel Doppler) at diagnosis. We divided the cohort into 2 groups, distinguishing between patients without cranial symptoms/signs (i.e., headaches, clinical temporal artery anomaly, jaw claudication, ophthalmologic symptoms) and those with cranial symptoms/signs. In the entire cohort of 143 patients, all of whom underwent vascular biopsy and vascular imaging, we detected 31 (22%) patients with no cranial symptoms/signs. In the latter, diagnosis was biopsy proven in an arterial sample in 23 cases (74% of patients, on a temporal site in 20 cases and on an extratemporal site in 3). One-third of these 31 patients displayed extracranial symptoms/signs whereas the remaining two-thirds presented only with constitutional symptoms and/or inflammatory laboratory test results. Compared to the 112 patients with cardinal cranial clinical symptoms/signs, patients without cranial manifestations displayed lower levels of inflammatory laboratory parameters (C-reactive level: 68 [9–250] mg/L vs 120 [3–120] mg/L; P  < 0.01), highest rate of aorta and aortic branch involvement identified (19/31 (61%) vs 42/112 (38%); P = 0.02) and also a lower rate of disease relapse (12/31 (39%) vs 67/112 (60%); P = 0.04). Our results suggest that patients without cranial symptoms/signs are prone to lower inflammatory laboratory parameters, fewer relapses, and more large-vessel involvement than those displaying cardinal cranial manifestations. Further studies are therefore required in order to determine whether these 2 subgroups of patients have a different prognosis, and therefore warrant different therapeutic and monitoring regimens.